Exclusionary practices in two-sided markets: The effect of radius clauses on competition between shopping centers - Tim Brühn; Georg Götz (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
This paper analyzes exclusionary conduct of platforms in two-sided markets. Motivated by recent antitrust cases against shopping centers introducing radius restrictions on their tenants, we provide a discussion of the likely positive and normative effects of exclusivity clauses, which prevent tenants from opening outlets in other shopping centers covered by the clause. In a standard two-sided market model with two competing shopping centers, we analyze incentives to introduce exclusivity clauses and the likely effects on social welfare. We show that exclusivity agreements are especially profitable for shopping centers and detrimental to social welfare if competition is intense between the two shopping centers. We argue that the focus of courts on market definition is misplaced in markets determined by competitive bottlenecks.
Keywords: D43; D62; L13; 330; platform competition; exclusive dealing; network effects; competitive bottlenecks